Dyspnoea and the ovaries: a rare presentation of Krukenberg tumour - Rawasia, Wasiq Faraz (BMJ Publishing Group, 2013)
Krukenberg tumour is a metastatic signet-ring adenocarcinoma of the ovary, usually with a gastrointestinal primary detected metachronously or synchronously. We present here a case of a 48 year-old woman who presented with a prolonged history of dyspnoea on exertion. Workup had revealed a pelvic mass. Thoracocentesis of her pleural effusion, with cytology, and pathology reports from her total abdominal hysterectomy with bilateral salpingo-oophorectomy revealed a carcinoma with signet-ring cells. Immunostains were positive for CDX2, CK7 and CK20, which was highly suggestive of a gastric primary. Colonoscopy was negative, and an oesophagogastroduodenoscopy revealed a few small crater ulcers, the biopsy of which was negative for cancer. A right-sided pleurodesis was performed for the unremitting malignant effusion, and a PleurX catheter was placed in her left pleural space. She was discharged home with a very poor prognosis.